Effect of partial root-zone drying irrigation (PRDI) on soil C:N:P stoichiometry in N-fixing crops: Insights from a three-year field study with alfalfa - Jing Zhang; Zheng Gang Guo (Agricultural Water Management)
Soil C:N:P stoichiometry is a powerful tool for determining soil nutrient cycling and limitations in agroecosystems and provides a basis for optimizing fertilizer strategies in crop production under partial root-zone drying irrigation (PRDI). PRDI is of particular interest in improving soil C:N:P stoichiometry in non-N-fixing crops because it enhances resource-use efficiency, which is critical for water management and soil health in arid agroecosystems. However, its effect on the soil C:N:P stoichiometry in N-fixing crops remains poorly understood. In this study, a three-year field experiment was conducted using alfalfa as a representative N-fixing crop to investigate the effect of PRDI on soil C, N, and P concentrations and their stoichiometry. The field experiment involved two irrigation methods, PRDI and conventional furrow irrigation (CFI), with four irrigation volumes set at 70 %, 85 %, 100 %, and 115 % evapotranspiration (ETc). This study showed that PRDI increased soil porosity, soil organic C and total N concentrations, decreased soil bulk density and did not affect soil total P concentrations. Furthermore, PRDI increased the soil C:N:P ratio and irrigation modes contributed more to the abovementioned variables than irrigation volumes. These findings suggest that PRDI might expose alfalfa to P limitation and present a pattern of how PRDI influences soil C:N:P stoichiometry in N-fixing crops. Therefore, this study provides valuable guidance for policymakers, agricultural practitioners, and researchers, with compelling evidence for developing sustainable water and nutrient management practices in the agroecosystems of arid regions.